(untitled) (Bangladesh Journal of Zoology, 2012)
Chironomid larvae are frequently available in the muddy habitats of Curzon Hall campus of University of Dhaka. The larvae of single species of Chironomus (Insecta: Diptera) were collected from the drains and pond of the campus. Algae, fungi, diatoms, protozoans, rotifers, animal parts (crustacean appendages, ostracodan shell, insect appendages), and detritus were found as the main food items of the larvae. Gut content analysis showed a change in their feeding habits with seasons. The feeding intensity was maximum in spring just after winter. The feeding activity was lowest in winter. The variation in the diet may suggest that these groups showed a low degree of selectivity, having more generalist food selection habit. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12902 Bangladesh J. Zool. 40(1): 129-133, 2012